Bridging the Gap: How Key Actors and Informal Practices Sustain Agrarian Reform in Indonesia’s Decentralized Governance - Raden Deden Dani Saleh; Novita Dian Lestari; Azka Aulia Putri Salsabila (Journal Public Policy, 2026)
This study examines how key actors and informal practices sustain the implementation of agrarian reform under Indonesia’s decentralized governance, focusing on the Agrarian Reform Task Force (GTRA). It aims to bridge the gap between formal institutional arrangements and actual policy outcomes by analyzing how collaboration unfolds in practice. Using a longitudinal qualitative design (2021–2024), the study draws on 45 in-depth interviews and policy document analysis across two contrasting districts—Sragen (high-performing) and Temanggung (low-performing). The analysis is guided by collaborative governance and multidimensional integration frameworks. The findings reveal three core dynamics. First, GTRA collaboration largely stagnates at the coordination level, with only 29% of forums producing actionable outcomes due to the absence of integrated systems and joint budgeting. Second, institutional dominance—particularly by the Land Office—creates informal “shadow hierarchies” that undermine horizontal collaboration. Third, informal personal networks play a decisive role, enabling 91% of successful initiatives but contributing to 63% of institutional memory loss following leadership rotation. The study concludes that agrarian reform is sustained through a paradoxical reliance on personalized leadership within fragmented systems. To address this, it proposes a hybrid governance model that institutionalizes adaptive leadership, codifies knowledge transfer, and embeds informal collaboration within formal structures. This approach offers a context-sensitive alternative to conventional models, emphasizing relational governance as a pathway to more resilient and inclusive policy implementation.